The Role of Academic Culture as an Intervention in Increasing the Influence of the Learning Environment on Student Self-Actualization - Sry Rosita; Muhmmad Farhan Andrean; Fitri Chairunnisa (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
This study purpose to determine the influence of the learning environment on student self-actualization with academic culture as an intervening variable. This type of research is quantitative research. The population in this study is the entirety students of the Program Study of Management of 2018-2020 totaled 592 person with a sample of 86 person. Data were collected using questionnaires. The data analysis method of this study is descriptive statistical analysis using the Structural Equation Model (SEM) technique, with Partial Least Square (PLS) as a tool to process it using the SmartPLS program (v.3.2.9). The results showed that the learning environment positively and significantly affects the self-actualization of students, the learning environment has a positive and significant effect on academic culture, academic culture has a positive and significant effect on student self-actualization and the learning environment has a positive and significant effect on student self-actualization through academic culture.